New Firms as Employers: The Wage Penalty for Voluntary and Involuntary Job Switchers. (1st May 2015) - Nyström, Kristina; Zhetibaeva Elvung, Gulzat
Abstract: According to previous research, new firms pay lower wages. However, previous studies have been unable to control for the possibility that the opportunity costs of accepting employment at new firms may differ across individuals. In this paper, we investigate whether a wage penalty for being employed at a new firm exists if we take the individual employee's experience and status in the labour market into consideration. We focus on individuals who decide to switch jobs and use matched employee–employer data about all firms and employees in Sweden for the period 1998–2010. Our results show that the share of job transitions into lower wages are higher for those who switch to new firms compared with incumbent firms (40 per cent and 31 per cent, respectively). Our endogenous wage equation estimates indicate that being an involuntary job switcher has an equally negative effect on wages at both new and incumbent firms. However, the positive effect of education on wages is more pronounced for job switchers selecting into incumbent firms.